Effect of repeated apoA-IMilano/POPC infusion on lipids, (apo)lipoproteins, and serum cholesterol efflux capacity in cynomolgus monkeys - Kempen, Herman J. (The American Society for Biochemistry and Molecular Biology, 2013)
MDCO-216, a complex of dimeric recombinant apoA-IMilano (apoA-IM) and palmitoyl-oleoyl-phosphatidylcholine (POPC), was administered to cynomolgus monkeys at 30, 100, and 300 mg/kg every other day for a total of 21 infusions, and effects on lipids, (apo)lipoproteins, and ex-vivo cholesterol efflux capacity were monitored. After 7 or 20 infusions, free cholesterol (FC) and phospholipids (PL) were strongly increased, and HDL-cholesterol (HDL-C), apoA-I, and apoA-II were strongly decreased. We then measured short-term effects on apoA-IM, lipids, and (apo)lipoproteins after the first or the last infusion. After the first infusion, PL and FC went up in the HDL region and also in the LDL and VLDL regions. ApoE shifted from HDL to LDL and VLDL regions, while ApoA-IM remained located in the HDL region. On day 41, ApoE levels were 8-fold higher than on day 1, and FC, PL, and apoE resided mostly in LDL and VLDL regions. Drug infusion quickly decreased the endogenous cholesterol esterification rate. ABCA1-mediated cholesterol efflux on day 41 was markedly increased, whereas scavenger receptor type B1 (SRB1) and ABCG1-mediated effluxes were only weakly increased. Strong increase of FC is due to sustained stimulation of ABCA1-mediated efflux, and drop in HDL and formation of large apoE-rich particles are due to lack of LCAT activation.